Pengaruh Samsat Keliling, Samsat Care, Sosialisasi Perpajakan, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Pada Kantor Samsat Makassar I - Apriliani, Lili; Hamzah, Hajrah; Nuraisyiah, Nuraisyiah (JURNAL ONLINE INSAN AKUNTAN; Vol 10 No 1 (2025): Jurnal Online Insan Akuntan (Juni 2025)DO - 10.51211/joia.v10i1.3451, 2025)
This study aims to analyze the effect of SAMSAT Mobile and SAMSAT Care services, as well as the relationship between Taxation Socialization and Tax Sanctions on Motor Vehicle Taxpayer Compliance registered at the Makassar I SAMSAT Office. The variables in this study are SAMSAT Mobile (X1), SAMSAT Care (X2), Taxation Socialization (X3), Tax Sanctions (X4), and Taxpayer Compliance (Y). The population in this study were all taxpayers registered at the Makassar I SAMSAT Office. Sampling using purposive sampling technique with the provision of taxpayers making tax payments at SAMSAT Keliling and SAMSAT Care until 100 respondents were obtained. Data collection techniques in the form of questionnaires and documentation. The data analysis technique used SPSS 27 and the tests carried out were normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, validity test, reliability test, t test, F test, multiple linear regression analysis, and coefficient of determination. The results showed that SAMSAT Mobile, SAMSAT Care, Tax Socialization, and Tax Sanctions each had a positive and significant effect both partially and simultaneously, with the more dominant Tax Sanctions variable.   Keywords : SAMSAT keliling, SAMSAT care, tax socialization, tax sanctions, taxpayer compliance